Effects of a 12-Week Resistance Training Program on Arterial Stiffness: A Randomized Controlled Trial. Issue 12 (December 2021) - Werner, Timothy J.; Pellinger, Thomas K.; Rosette, Vincent D.; Ortlip, Austin T.
Abstract: Werner, TJ, Pellinger, TK, Rosette, VD, and Ortlip, AT. Effects of a 12-week resistance training program on arterial stiffness: a randomized controlled trial. J Strength Cond Res 35(12): 3281–3287, 2021—Arterial stiffness is an indicator of disease and is an independent predictor of cardiovascular events. Some reports indicate that resistance training increases indices of arterial stiffness, whereas others report no association. This study sought to determine the association between 2 common resistance training models and indices of arterial stiffness. We recruited 30 male, untrained subjects (18–30 years) and randomized them into 1 of 3 groups: control (CON, n = 10), high-intensity resistance exercise (HI, n = 10), and high-volume resistance exercise (HV, n = 10). Subjects randomized to the resistance training groups were required to perform whole-body strength training exercises 3–5 days a week for 12 weeks. The exercise regimen consisted of 2–3 sets of 3–8 repetitions (80–90% of 1 repetition maximum [1RM]) for the HI group and 3–4 sets of 10–15 repetitions (50–70% of 1RM) for the HV group. Anthropometry, carotid artery diameters, peripheral and central blood pressure, and maximal dynamic strength were measured before and after the 12-week study period. Subjects were instructed to maintain their normal diet and avoid aerobic exercise during the study. After the intervention, both the HI and HV groups increased their maximal strength on the back squat, bench press, and seated row (all p < 0.05). However, there were no changes in arterial stiffness indices between the groups. Using a randomized controlled trial with validated measurements of arterial stiffness, chronic resistance training does not appear to influence central arterial stiffness, regardless of training volume and load.